Low threading dislocation density and antiphase boundary free GaAs epitaxially grown on on-axis Si (001) substrates. Issue 46 (14th November 2022) - Yang, Junjie; Li, Keshuang; Jia, Hui; Deng, Huiwen; Yu, Xuezhe; Jurczak, Pamela; Park, Jae-Seong; Pan, Shujie; Li, Wei; Chen, Siming; Seeds, Alwyn; Tang, Mingchu; et al.
Abstract : The interactions between 1D defect threading dislocations and 2D defect antiphase boundaries and antiphase boundary annihilation in III–V materials on Si heteroepitaxy growth are revealed. Abstract : Epitaxial growth of III–V materials on a CMOS-compatible Si (001) substrate enables the feasibility of mass production of low-cost and high-yield Si-based III–V optoelectronic devices. However, the material dissimilarities between III–V and group-IV materials induce several types of defects, especially threading dislocations (TDs) and antiphase boundaries (APBs). The presence of these defects is detrimental to the optoelectronic device performance and thus needs to be eliminated. In this paper, the mechanism of APB annihilation during the growth of GaAs on on-axis Si (001) is clarified, along with a detailed investigation of the interaction between TDs and the periodic 110 APBs. A significant reduction in the TD density ascribed to the presence of periodic APBs is discussed. This new observation opens the possibility of reducing both APBs and TDs simultaneously by utilising optimised GaAs growth methods in the future. Hence, a thin APB-free GaAs/Si (001) platform with a low TD density (TDD) was obtained. Based on this platform, a high-performance high-yield III–V optoelectronic device grown on CMOS-compatible Si (001) substrates with an overall thickness below the cracking threshold is feasible, enabling the mass production of Si-based photonic integrated circuits (PICs).